Stepping stones or stone dead? Fecundity, pollen dispersal and mating patterns of roadside Qualea grandiflora Mart. trees - Potascheff, CM; Oddou-Muratorio, S; Klein, EK; Figueira, A; Bressan, EA; Oliveira, PE; Lander, T; Sebbenn, AM (Springer Nature, 2019)
Forest fragmentation may affect mating and pollen dispersal patterns through conversion of continuous forests into small, spatially isolated remnant patches and individual trees in an anthropogenic landscape. We investigated reproductive investment and success, pollen dispersal, mating system, and genetic diversity and spatial structure of Qualea grandiflora trees in two environmental contexts: a continuous natural Cerrado area and isolated individuals on roadsides. Roadside trees produced more flowers and more fruit than Cerrado trees. Pollen dispersal kernels were fat-tailed in both contexts, indicating long-distance dispersal, but in Cerrado the mean pollen dispersal distance (524.7 m) and the effective number of pollen donors per mother-tree (Nep = 12.7) were higher than for roadside trees (60.9 m, Nep = 4.6). The levels and structure of genetic diversity, outcrossing rates (tm > 0.98), and mating among relatives (tm- ts < 0.1) were similar in both environmental contexts. Allelic richness and number of private alleles were similar between the two environments. The fixation index was significantly lower in adults (minimum of 0.08) than in offspring (minimum of 0.23) in both contexts, suggesting selection against inbred individuals between offspring and adult stage. Our results indicate that the spatial isolation of roadside trees, by increasing the number of flowers produced, decreased pollinator movements, thereby reducing effective pollen flow and the number of pollen donors. All these results suggest that roadside trees can be used for harvesting seeds for recovery plans, and that these trees are a biological legacy, and reservoir of Q. grandiflora genetic diversity, from the original Cerrado forest.